Isolation and characterization of aerobic and anaerobic bacteria from satay and otak-otak in Kuala Pilah / Fatin Nadhira Noorhizam - Noorhizam, Fatin Nadhira (2017)
Satay and Otak-otak were very famous street food that can easily be found at many places. Without correct supervision, the food can easily contaminated by pathogenic bacteria. The aim of this study was to isolate the bacteria from satay and Otak-otak in Kuala Pilah. It is also to identify and characterize the aerobic and anaerobic bacteria that grow in the satay and Otak-otak. In this study, the results shown that all bacteria isolates were Gram-Negative bacteria after performed the Gram Stain. Two biochemical tests which catalase and oxidase test were performed and the results were catalase-positive and oxidase-negative for all bacteria isolates. Therefore, it can be concluded that the bacteria isolates were facultative anaerobes. The bacteria isolates also can be group under family Enterobacteriacae. It was recommended to use selective and differential media to get the specific species of pathogenic bacteria and perform more biochemical tests